2015
DOI: 10.22302/ppk.wp.v34i1.60
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Sifat Kimia Abu Vulkanik Dan Upaya Pemulihan Tanaman Karet Terdampak Letusan Gunung Kelud (Studi Kasus: Kebun Ngrangkah Pawon, Jawa Timur)

Abstract: Indonesia merupakan daerah yang dikelilingi oleh pegunungan berapi paling aktif di dunia, yang tersebar di berbagai pulau. Pada awal tahun 2014 yang lalu, Gunung Kelud di Kediri, Jawa Timur meletus sehingga menimbulkan kerusakan di sekitarnya, termasuk perkebunan Ngrangkah Pawon. Meskipun demikian, dalam jangka panjang material vulkanik sangat bermanfaat untuk perkebunan karena dapat menyuburkan tanah. Abu vulkanik merupakan mineral yang memiliki potensi sebagai pembenah tanah sekaligus berfungsi memperkaya ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…However, the ability to control resource allocation to nodules may be less important to Parasponia hosts, given the extremely nutrient poor soils in which they are typically found (Achmad and Hadi, 2016). In this ecological niche, we would not expect hosts to be exposed to high nitrogen conditions, nor the concurrent selection pressures against nodulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to control resource allocation to nodules may be less important to Parasponia hosts, given the extremely nutrient poor soils in which they are typically found (Achmad and Hadi, 2016). In this ecological niche, we would not expect hosts to be exposed to high nitrogen conditions, nor the concurrent selection pressures against nodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Remarks: +Ash = location with volcanic ash input, -Ash = location without ash input, SF = Natural (secondary) forest, AFM = multistrata agroforestry, AFS = simple agroforestry, TS = annual crops Beyond the directly negative effects, however, ash can be a source of plant nutrients. Achmad & Hadi (2015) reported that Mount Kelud volcanic ash entering a rubber plantation in Ngrangkah, Pawon (PTPN XII-Persero) was considered beneficial for rubber plants because the pH of volcanic ash was rather acidic (pH 5.0-6.0) which was ideal for rubber plants; chemical properties of the ash, with P-Bray1 levels of 38 mg/kg (classified as very high), Ca levels of 4.8 cmol/kg (very high), and a K level of 0.45 cmol/ kg (moderate) provides for all plant needs except for N. These properties of volcanic ash indicate the driving force of the local evolution of symbiotic nitrogen fixation that the Trema -Parasponia pairing suggests; any gain in N supply by Parasponia is important in this volcanic ash environment, while the pioneer tree properties shared with Trema allow rapid seedling establishment and growth.…”
Section: Copyright © 2020 Universitas Brawijayamentioning
confidence: 99%
“…Di dalam abu vulkanik tersebut mengandung berbagai macam unsur seperti S, Al, Fe, pH yang masam, dan unsur-unsur utama yang tersedia dalam jumlah yang rendah sehingga menyebabkan para petani kesulitan untuk mengolah tanah tersebut (Hanifah, 2016). Nilai pH tanah abu vulkanik Gunung Kelud tergolong masam, hal ini dapat dilihat dari nilai pH yang berkisar 5-6 dan tergolong agak masam bila dibandingan dengan abu vulkanik yang berasal dari Gunung Merapi (Achmad dan Hadi, 2015). Salah satu upaya untuk mengatasi masalah ketersediaan unsur hara adalah dengan aplikasi bahan organik.…”
Section: Pendahuluanunclassified